Harvesting change: The impact of climate change on Africa’s agriFood systems - Piñeiro, Valeria; Gianatiempo, Juan Pablo; McNamara, Brian; Thomas, Timothy S.; Traoré, Fousseini (International Food Policy Research Institute, 2025)
Africa is one of the most exposed continents to climate change. While global temperature has risen by 0.2°C per decade since 1991, in Africa the rate is faster, reaching 0.3°C (WMO 2022). Yet Africa contributes only modestly to climate change. Indeed, the continent emits 7 times less greenhouse gas compared to Europe and 15 times compared to North America (IPCC, 2023). In addition to rising temperatures, climate change affects Africa through several channels, including an increase in ocean levels, variations in precipitations (droughts and heavy rains), plant pests and animal diseases. Climate change is also expected to contribute to a significant reduction in arable land in the continent (IPCC, 2023). The new CAADP strategy and action plan for 2026-2035 recognizes that Africa is the hardest hit by climate change and that the phenomenon is one of the major threats to Africa’s agricultural systems and food security in the coming years.